Celso Furtado e sua compreensão do subdesenvolvimento: uma análise da evolução de seu pensamento - Pimenta, Alanna Santos de Oliveira (2013)
With this study, we aim at making a synthesis of Celso Furtados s thought in relation to his underdevelopment interpretation and his correspondent proposal of overcoming this phenomenon. With this attempt, we aim at identifying the features of linearity and/or change present in his ideas about the mentioned theme. This purpose is justified by the fact that uncountable events happened during more than half a century of study of the underdevelopment condition dedicated by the author. Among them, the one which can be characterized as a temporal divisor in his thought, considered in this study, is the trasnationalization process. We intend to show that this new way that globalization assumes dictates new limits to peripheral economies development, as Furtado showed, and these limits jeopardize the overcome proposal the author had. Besides that, the dependence symptom, which underdeveloped structures are historically hostages, and that is usually explored by the author, turns to be taken to cultural value terms, turning out to be, in his vision, more perverse to the development attempt. Finally, we aim at demonstrating that, although the transnationalization process has broken with Furtado s overcoming proposal of underdevelopment, represented by the National State conformation, and despite it has taken him to denote new values to dependence, the underdevelopment essence is still the same in his analyses.